Chemical elements in sediments and in bivalve mollusks from estuarine regions in the south of Bahia State, northeast Brazil - Santos,G. B. M. (2023)
Abstract Estuaries receive daily inputs of chemical elements which can impact the quality of water and sediment, as well as the health of biota. In addition to the sediment, bivalve mollusks have been used in the chemical monitoring of these systems. This study investigated the presence and contents of As, Ba, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb and Zn in superficial sediment and in bivalves (Crassostrea gasar, C. rhizophorae and Mytella guyanensis) from estuaries in the south / extreme south of Bahia State, northeast Brazil. The samples were evaluated with inductively coupled plasma optical emission spectrometry (ICP-OES, Varian 710). Except for Cd, all other elements were found in the samples, being that Co was exclusive in the sediment. The estuaries equivalent to sampling stations #1 - Valença, #2 - Taperoá, #3 - Ilhéus and #4 - Belmonte showed levels of metals compatibles with those established by the Brazilian legislation, however, the #5 - Santa Cruz Cabrália, in addition to the presence of As, presented a high level of Pb and Cu in C. gasar, which was attributed to the impacts of nautical activities in that locality.